Identification of a New Mullet Species Complex Based on an Integrative Molecular and Cytogenetic Investigation of Mugil hospes (Mugilidae: Mugiliformes) - Nirchio, Mauro; Paim, Fabilene G.; Milana, Valentina; Rossi, Anna R.; Oliveira, Claudio (Frontiers in Genetics, 2018)
Mullets are very common fishes included in the family Mugilidae, (Mugiliformes), which are characterized by both a remarkably uniform external morphology and internal anatomy. Recently, within this family, different species complexes were molecularly identified within Mugil, a genus which is characterized by lineages that sometimes show very different karyotypes. Here we report the results of cytogenetic and molecular analyses conducted on Mugil hospes, commonly known as the hospe mullet, from Ecuador. The study aims to verify whether the original described species from the Pacific Ocean corresponds to that identified in the Atlantic Ocean, and to identify species-specific chromosome markers that can add new comparative data about Mugilidae karyotype evolution. The karyotype of M. hospes from Ecuador is composed of 48 acrocentric chromosomes and shows two active nucleolar organizer regions (NORs). In situ hybridization, using different types of repetitive sequences (rDNAs, U1 snDNA, telomeric repeats) as probes, identified species-specific chromosome markers that have been compared with those of other species of the genus Mugil. Cytochrome c oxidase subunit I (COI) sequence analysis shows only 92-93% similarity with sequences previously deposited under this species name in GenBank, all of which were from the Atlantic Ocean. Phylogenetic reconstructions indicate the presence of three well-supported hospe mullet lineages whose molecular divergence is compatible with the presence of distinct species. Indeed, the first lineage includes samples from Ecuador, whereas the other two lineages include the Atlantic samples and correspond to M. brevirostris from Brazil and Mugil sp. R from Belize/Venezuela. Results here provided reiterate the pivotal importance of an integrative molecular and cytogenetic approach in the reconstruction of the relationships within Mugilidae.